VERTICAL NATURATION TECHNOLOGY AND ITS EFFECT ON COMFORT THERMAL IN COMMERCIAL BUILDINGS IN LIMA - Condori Huamán, Fredy Porfirio (2025)
The purpose of this research was to analyze the effects of vertical nature on thermal comfort, within the Centro Lima commercial building, located in the district of Lima, using the Kestrel 5500 mini weather station and temperature and humidity recorders, with the purpose of proposing vertical nature (vertical gardens) inside commercial buildings of Metropolitan Lima. For which a pilot pilot design was used, reaching the following conclusions: theenvironmental conditions of thermal comfort within the commercial building underinvestigation do not comply with the minimum safety and health provisions in workplaces, since they exceed the temperature levels and there is low humidity with low wind speed. The installed vertical nature favorably affects thermal comfort within the commercial building, regulating the basic parameters and placing them within the minimum health and safety regulations in workplaces.